CONTINUOUS AND IMPACT CUTTING SYSTEMS FOR SUGARCANE HARVESTER - Filho, Aldir C. Marques [UNESP]; Testa, João V. P. [UNESP]; Moura, Michel S. [UNESP]; Martins, Murilo B.; Lanças, Kléber P. [UNESP] (FapUNIFESP (SciELO), 2022)
The quality of the basal cut of sugarcane during harvest can affect the longevity of the crop, and the cutting tool is one of the main causes of damage during harvesting. The aim of this study was to evaluate the performance of two cutting tools: an impact cutting system (ICS) using knives and a continuous cutting system (CCS) using saws. Laboratory tests were carried out to obtain the stalk damage index at different device travel speeds and to determine the invisible losses caused by each cutting system. The results showed that both cutting systems presented acceptable levels for the stalk damage index; however, the CCS obtained better cut quality, corresponding with decreased general damage. The invisible losses caused by the cutting tools in relation to the total harvested mass were 0.52% and 0.54% for the CCS and ICS, respectively. The highest invisible losses were obtained at speeds of 2, 3, and 4 km h-1 for the ICS, showing a statistical difference in relation to the CCS. No statistical difference was noted for both the systems at 5 and 6 km h-1.
Keywords: Damage index; Invisible losses; Mechanized harvester; Saccharum officinarum